2010
DOI: 10.5271/sjweh.3122
|View full text |Cite
|
Sign up to set email alerts
|

A phase-advanced, extended sleep paradigm to increase sleep duration among early-morning shift workers: a preliminary investigation

Abstract: Yeung J, Sletten TL, Rajaratnam SM. A phase-advanced, extended sleep paradigm to increase sleep duration among early-morning shift workers: a preliminary investigation. Scand J Work Environ Health. 2011;37(1):62-69 Objective In this preliminary study, using a within-subjects design, we investigated the effects of phaseadvancing bedtime on sleep quality and duration among early-morning shift workers. MethodsThe sleep-wake patterns of 16 healthy volunteers who work shifts with start times between 04.00-07.30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“… 64 66 Good design of work hours would include later shift start times (≥7 am ) and more time between shifts (≥12 hours) when possible. 67 These guidelines may be easier to implement during Project Fire rather than Initial Attack deployments due to the nature of the fire suppression activities. For Initial Attack suppression, it may be wise to limit the shortened sleep periods as much as possible to reduce performance deficits and fatigue-related errors in judgment.…”
Section: Discussionmentioning
confidence: 99%
“… 64 66 Good design of work hours would include later shift start times (≥7 am ) and more time between shifts (≥12 hours) when possible. 67 These guidelines may be easier to implement during Project Fire rather than Initial Attack deployments due to the nature of the fire suppression activities. For Initial Attack suppression, it may be wise to limit the shortened sleep periods as much as possible to reduce performance deficits and fatigue-related errors in judgment.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, one study evaluated the effectiveness of prescribing a bedtime ten hours prior to the start time of the following shift. The prescription of bedtime resulted in increased objective sleep duration and increased subjective sleep duration and quality [116]. Further, the sample for this study was small (n = 16) but did investigate a range of occupations (manufacturing, customer service, nursing, and public service).…”
Section: Behavioural Interventionsmentioning
confidence: 99%
“…This is not surprising-while shift work may be a common feature for these workers, individual differences in occupation, sociodemographic characteristics, job demands, and health status likely call for unique interventions. Broadly, objective sleep measures were improved by controlled light exposure including intermittent bright light [123,130], bright light and light-blocking goggles [119,126,129,130], light-blocking goggles alone [125], schedule change which increased recovery periods [87,92,96] and prescriptive sleep scheduling [116]. Subjective measures of sleep were improved by a change to 12 h shifts (e.g., two-shift system) [70,88,89,91,93,97], a change to forward rotation schedules [78,80,83,90], increased rest or recovery periods [75,79], individualised behavioural intervention aimed at improving sleep and fatigue [106,115], and some complementary therapies (e.g., electrical acupoint stimulation and aromatherapy massage) [131,134].…”
Section: Qualitative Findingsmentioning
confidence: 99%
“…Morning shifts starting between 04.00 and 07.00 hours are particularly associated with disturbances in the sleep-wake pattern during and outside shifts. [1][2][3] Yeung et al 4 have shown that total sleep time was reduced by 1.4 hours during morning shift work. Folkard et al 5 found that for a shift worker to get a full 8-hours sleep period before their morning shift they would have to leave home at 8 o'clock in the morning.…”
Section: Introductionmentioning
confidence: 99%